1986
DOI: 10.1056/nejm198606123142404
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vasodilator Therapy on Mortality in Chronic Congestive Heart Failure

Abstract: To evaluate the effects of vasodilator therapy on mortality among patients with chronic congestive heart failure, we randomly assigned 642 men with impaired cardiac function and reduced exercise tolerance who were taking digoxin and a diuretic to receive additional double-blind treatment with placebo, prazosin (20 mg per day), or the combination of hydralazine (300 mg per day) and isosorbide dinitrate (160 mg per day). Follow-up averaged 2.3 years (range, 6 months to 5.7 years). Mortality over the entire follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
248
0
17

Year Published

1991
1991
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 2,194 publications
(267 citation statements)
references
References 27 publications
2
248
0
17
Order By: Relevance
“…72 Additionally, in VeHFT (Veterans Heart Failure Trial-1), hydralazine combined with isosorbide dinitrate decreased mortality and improved LVEF compared with placebo, whereas prazosin did not. 73 …”
Section: Antihypertensive Medications α 1 -Blockersmentioning
confidence: 99%
See 1 more Smart Citation
“…72 Additionally, in VeHFT (Veterans Heart Failure Trial-1), hydralazine combined with isosorbide dinitrate decreased mortality and improved LVEF compared with placebo, whereas prazosin did not. 73 …”
Section: Antihypertensive Medications α 1 -Blockersmentioning
confidence: 99%
“…In the case of the nonuroselective agents, which have greater systemic α-blockade effects, much of the evidence has been extrapolated from the results of ALLHAT and Ve-HFT-1. 71,73 In a retrospective analysis of 388 patients with HF and benign prostatic hypertrophy receiving prazosin, terazosin, doxazosin, or tamsulosin, Dhaliwal et al 281 found no significant increase in all-cause mortality and HF rehospitalization in those receiving β-blockers. However, in those not receiving β-blockade, α-blockade exposure was associated with an increase in HF hospitalization (HR, 1.94; 95% CI, 1.14-3.32).…”
Section: Antimalarial Agentsmentioning
confidence: 99%
“…The V‐HeFT I trial compared hydralazine and ISDN versus prazosin with placebo in 642 men with impaired systolic function and demonstrated a 34% relative risk reduction at 2 years ( P  < 0.028) (Cohn et al ., 1986). V‐HeFT II was undertaken in 1991 to compare this combination with and without enalapril, with significant mortality benefit seen in the enalapril arm (Cohn et al ., 1991).…”
Section: Evidence‐based Pharmacological Agentsmentioning
confidence: 99%
“…Ironically, the combination of hydralazine and isosorbide dinitrate actually proved to be nearly inferior to an ACE inhibitor on survival in the patients with mild-to-moderate heart failure enrolled in the V-HeFT II trial, 20 even though the effects of an ACE inhibitor on mortality in such patients are known to be modest (when compared with placebo). 21 Interestingly, the effect of hydralazine and isosorbide dinitrate on the risk of death and heart failure hospitalizations was not a prespecified end point in either V-HeFT I or V-HeFT II, 20,22 and the combined data from V-HeFT I and V-HeFT II were sufficiently confusing that the FDA declined to approve the combination for the treatment of chronic heart failure when the initial application for its commercial use was made in 1997. 23 At the same time, the guideline process has been silent on 2 drugs that were approved for the treatment of heart failure in the United States >6 months ago, ivabradine and sacubitril/valsartan.…”
Section: Packermentioning
confidence: 99%